Indonesian Fan Girls’ Perception towards Soft Masculinity as Represented By K-pop Male Idols - Ayuningtyas, Paramita (Lingua Cultura, 2017)
This article aimed to examine how fan girls perceive this new form of masculinity represented by K-pop male idols (termed as soft masculinity). This research used a mixed method in collecting the data from a questionnaire distributed via e-mail and Line to twenty fan girls from various fandoms in April 2016. The result shows that the respondents are aware that in the entertainment business, gender identity can be modified and presented as a part of marketing strategy. In addition, they only see the soft masculinity delivered by K-pop male idols as a form of performance.